(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Alfred Mahan is regarded as one of the main exponents of naval strategy in operational and tactical terms. But underlying these considerations, his work contains other important messages about the creation of naval power that should not be eclipsed by them, beginning with the role of geography, which, although not decisive when it comes to selecting major global powers, can nonetheless play a key role by ruling out certain states. However, these precepts vouch for a strategist concerned with issues of a sociological, economic and political nature, which he translates into conditions enabling ultimate military success, thus escaping the temptation of determinism.